Short and long-term immune changes in different severity groups of COVID-19 disease - Khuloud Al Maamari; Ibrahim Al Busaidi; Mahmood Al Kindi; Fahad Zadjali; Fatma BaAlawi; Wijesinghe Anesta; Kawthar Al Amri; Wafa Albalushi; Hamed Al Balushi; Ayman Al Amri; Mahmood Aljufaili; Mujahid Al-Busaidi; et al. (International Journal of Infectious Diseases, 2022)
Background: There are limited data on short- versus long-term changes in adaptive immune response across different COVID-19 disease severity groups. Methods: A multicenter prospective study of 140 adult patients with COVID-19 (a total of 325 samples) were analyzed for inflammatory markers and lymphocyte subsets at presentation, week 2, and week 24. Results: Inflammatory markers at presentation were higher in the critical/severe than in moderate and mild groups. A predominance of memory B cell response in the mild and moderate group was noted by week 2. In contrast, the immune system in the severe/critical group was dysfunctional, with expansion of exhausted CD8+ T cells and atypical memory B cells. By 24 weeks, there was a possible trend of normalization. Conclusion: There was substantial difference in the degree of inflammation and distribution of different B and T cell subsets in the different disease severity groups. Despite the initial dysfunctional immune response in the severe/critical group, a comparable memory B and CD8+ T cell responses to the mild group was achieved at 24 weeks.